Media Informasi Masjid Sebagai Sarana Standarisasi Informasi Masjid Attharuf Kepada Masyarakat - Cahya Rahmad; Septian Enggar Sukmana; Annisa Puspa Kirana; Moh. Zawaruddin Abdullah; Vivin Ayu Lestari; Triana Fatmawati (P3M Politeknik Negeri Malang, 2025)
Mosques play a vital role as centers of worship and socio-religious activities. However, information dissemination often goes unnoticed, even when shared through messaging applications. Baital Ma'ruf Mosque in Malang Regency faces similar challenges. Therefore, a mosque information display system was implemented. This community service program aims to standardize information and make it easier for mosque administrators to update content in real-time. The results of this initiative show that 85% of congregants feel it's now easier to get information. The Baital Ma'ruf Mosque administrators have responded very positively, affirming that this mosque information system brings significant benefits to both congregants and the wider community, making it an innovative solution for the mosque's digital transformation.